Deletion of B-cell translocation gene 2 (BTG2) alters the responses of glial cells in white matter to chronic cerebral hypoperfusion - Kaoru Suzuki; Mitsuru Shinohara; Yoshihiro Uno; Yoshitaka Tashiro; Ghupurjan Gheni; Miho Yamamoto; Akio Fukumori; Akihiko Shindo; Tomoji Mashimo; Hidekazu Tomimoto; Naoyuki Sato (Journal of Neuroinflammation, 2021)
Abstract Background Subcortical ischemic vascular dementia, one of the major subtypes of vascular dementia, is characterized by lacunar infarcts and white matter lesions caused by chronic cerebral hypoperfusion. In this study, we used a mouse model of bilateral common carotid artery stenosis (BCAS) to investigate the role of B-cell translocation gene 2 (BTG2), an antiproliferation gene, in the white matter glial response to chronic cerebral hypoperfusion. Methods Btg2 −/− mice and littermate wild-type control mice underwent BCAS or sham operation. Behavior phenotypes were assessed by open-field test and Morris water maze test. Brain tissues were analyzed for the degree of white matter lesions and glial changes. To further confirm the effects of Btg2 deletion on proliferation of glial cells in vitro, BrdU incorporation was investigated in mixed glial cells derived from wild-type and Btg2 −/− mice. Results Relative to wild-type mice with or without BCAS, BCAS-treated Btg2 −/− mice exhibited elevated spontaneous locomotor activity and poorer spatial learning ability. Although the severities of white matter lesions did not significantly differ between wild-type and Btg2 −/− mice after BCAS, the immunoreactivities of GFAP, a marker of astrocytes, and Mac2, a marker of activated microglia and macrophages, in the white matter of the optic tract were higher in BCAS-treated Btg2 −/− mice than in BCAS-treated wild-type mice. The expression level of Gfap was also significantly elevated in BCAS-treated Btg2 −/− mice. In vitro analysis showed that BrdU incorporation in mixed glial cells in response to inflammatory stimulation associated with cerebral hypoperfusion was higher in Btg2 −/− mice than in wild-type mice. Conclusion BTG2 negatively regulates glial cell proliferation in response to cerebral hypoperfusion, resulting in behavioral changes.